2010
DOI: 10.1292/jvms.09-0401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Embryo Transfer following Artificial Insemination (ETFAI) on Reproductive Performance in Dairy Cows in South-Western Japan

Abstract: ABSTRACT. In order to improve the reproductive performance during the summer period, embryo transfer (ET; Japanese black embryo) following artificial insemination (AI; Holstein semen: ETFAI) was conducted in dairy cows in south-western Japan (n=56). The conception rate was improved in cows with ETFAI compared with conventional AI, which served as the control (n=195; 30.4% vs. 13.8%, P<0.01). However, higher fetal loss was observed in ETFAI compared with the controls (38.1% vs. 7.4%, P<0.05). Four cases of twin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
(21 reference statements)
0
5
0
1
Order By: Relevance
“…Posisi embrio dengan metode IB-TE masih diperdebatkan. Tani et al (2010) melaporkan bahwa IB-TE akan menghasilkan kelahiran kembar lebih tinggi, dengan cara contralateral dimana TE dilakukan pada posisi berlawanan dengan letak Corpus Luteum (CL), dibandingkan ipsilateral atau searah dengan CL (58% vs 32%). Tetapi Yoon et al (2012) menganjurkan sebaliknya bahwa untuk menghasilkan anak kembar IB-TE sebaiknya posisi embrio ipsilateral.…”
Section: Kombinasi Ib-teunclassified
“…Posisi embrio dengan metode IB-TE masih diperdebatkan. Tani et al (2010) melaporkan bahwa IB-TE akan menghasilkan kelahiran kembar lebih tinggi, dengan cara contralateral dimana TE dilakukan pada posisi berlawanan dengan letak Corpus Luteum (CL), dibandingkan ipsilateral atau searah dengan CL (58% vs 32%). Tetapi Yoon et al (2012) menganjurkan sebaliknya bahwa untuk menghasilkan anak kembar IB-TE sebaiknya posisi embrio ipsilateral.…”
Section: Kombinasi Ib-teunclassified
“…1999). In Kumamoto Prefecture where it is very hot in summer, transfer of an IVP Japanese Black embryo following AI of Holstein semen in dairy cows resulted in greater pregnancy rates than those after conventional AI (Tani et al . 2010).…”
Section: Embryo Transfer To Overcome Heat Stressmentioning
confidence: 99%
“…In Florida, USA, a Tdb of 29.7°C was associated with an average rectal temperature of 39°C (mild hyperthermia), and a Tdb of 31.4°C was associated with an average rectal temperature of 39.5°C (Dikmen & Hansen 2009). Using dairy cows in south-western Japan (Kumamoto prefecture), Tani et al (2010) reported that pregnant cows had lower rectal temperature than non-pregnant cows at day 7 (38.7°C vs. 39.4°C, P < 0.05) or 8 (38.8°C vs. 39.1°C, P < 0.05) after artificial insemination (AI). Probably the best method for assessing HS is to measure rectal temperatures and respiration rates during the afternoon in a few sentinel cows.…”
Section: Evaluation Indices Of the Magnitude Of Hs In Summermentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, transferring beef cattle embryos to dairy cattle is a common means of augmenting income among farmers and also avoids accidents associated with delivery in heifers [ 25 ]. It is effective for producing thermotolerant embryos that can be implanted after embryo transfer even under high temperatures.…”
mentioning
confidence: 99%